Automatic periodical SO2 fumigation improves the storage quality of tender ginger. Issue 4 (17th February 2021) - Jia, Xiaoyu; Du, Meijun; Zheng, Yanli; Chen, Lan; Song, Jianxin; Tang, Xianpu; Liu, Haidong; Li, Jiangkuo; Li, Xihong
Abstract: Rhizome rot and quality deterioration of tender ginger after harvest were the restricting factors of tender ginger storage quality. In this research, cold storage with SO2 fumigation function was designed and the effects of 0.2, 0.5, and 1.0 ml L −1 SO2 fumigation every 15 d on the storage quality of tender ginger was investigated. The improved cold storage and supporting equipment can automatically fill and remove SO2 gas into the storage room, and keep the humidity stable at 92%–95% during storage. Experimental results showed that automatic periodical SO2 fumigation of tender ginger with 0.5 ml L −1 SO2 every 15 d can effectively maintain firmness ( 56%), retard weight loss ( 22%), reduce decay rate ( 20%), and inhibit the accumulation of malondialdehyde (MDA) content ( 26%). Meanwhile, the 0.5 ml L −1 SO2 treatment enhanced the disease resistance of tender ginger by enhancing phenylalanine ammonia lyase (PAL) activity ( 8%) and inhibiting polyphenol oxidase (PPO) activity ( 25%), and the integrity of tissue structure was also well maintained. More importantly, the SO2 residue in the tender ginger treated with the 0.5 ml L −1 SO2 completely met the FDA food safety standard on the 50 d. Therefore, the combination of cold storage structure innovation and 0.5 ml L −1 SO2 periodical fumigation is more effective at improving the storage quality of tender ginger. Practical applications: Automatic periodical SO2 fumigation showed great potential application in maintaining the storage quality of ginger after harvest. The activity levels of defense enzymes were significantly increased and the storage quality of tender ginger was well maintained. Automatic periodical fumigation of tender ginger with 0.5 ml L −1 SO2 is a simple, safe, low cost, and convenient method to improve the storage quality of tender ginger.